Plasticity of the Reproductive Axis Caused by Social Status Change in an African Cichlid Fish: I. Pituitary Gonadotropins - Maruska, Karen P. (The Endocrine Society, 2011)
Social position in a dominance hierarchy is often tightly coupled with fertility. Consequently, an animal that can recognize and rapidly take advantage of an opportunity to rise in rank will have a reproductive advantage. Reproduction in all vertebrates is controlled by the brain-pituitary-gonad axis, and in males of the African cichlid fish Astatotilapia burtoni, GnRH1 neurons at the apex of this axis are under social control. However, little is known about how quickly social information is transformed into functional reproductive change, or about how socially controlled changes in GnRH1 neurons influence downstream actions of the brain-pituitary-gonad axis. We created an opportunity for reproductively suppressed males to ascend in status and then measured how quickly the perception of this opportunity caused changes in mRNA and protein levels of the pituitary gonadotropins. mRNA levels of the β-subunits of LH and FSH rose rapidly in the pituitary 30 min after suppressed males perceived an opportunity to ascend. In contrast, mRNA levels of GnRH receptor-1 remained unchanged during social transition but were higher in stable dominant compared with subordinate males. In the circulation, levels of both LH and FSH were also quickly elevated. There was a positive correlation between mRNA in the pituitary and circulating protein levels for LH and FSH, and both gonadotropins were positively correlated with plasma 11-ketotestosterone. Our results show that the pituitary is stimulated extremely rapidly after perception of social opportunity, probably to allow suppressed males to quickly achieve reproductive success in a dynamic social environment.